(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The objective of the research is to identify the efficiency of risk management in various names at Baghdad International Airport in the face of various risks (financial - technical - human - natural ..) facing the sample of the search of the General Establishment of Civil Aviation and the Iraqi Airways Company where the researcher identified the hypothesis that summarizes There is a significant significant correlation between risk management, risk management and risk review and assessment. The researcher used the means of research from observation and interviews with the relevant officials in this field, as well as used the questionnaire and distributed a sample of 170 employees in the field of risk management (SMS Department) in Iraqi Airways, Industrial Security, Insurance Department, Engineers, Technicians (250) were analyzed using statistical analysis according to the spss system, the Likert pentagram, the arithmetic mean, the standard deviation, the coefficient of variation, and the relative importance of achieving its goals.The researcher concluded from this to the validity of the hypothesis in the existence of a strong positive correlation between the risk management and risk management at the civil airports - Baghdad International Airport research sample at the macro level. The researcher reached a number of conclusions, the most important of which are: Risk management plays a big role in the future of the airport by drawing it for future vision and defining the mission and objectives of the organization and its ability to think and strategic analysis and strategic decision-making and its responsibility in formulating a future plan and then implementation and evaluation. There is no specialized risk management department within the organizational structure of the Civil Aviation General Establishment and Iraqi Airways, but there are different forms such as safety management, industrial security, etc., and they have an active role in the airport in the exercise of its duty. There is a lack of expertise and technical team, both in the number or quality of experience at the level of application of risk and insurance management and the insurance department in particular and the airport sample research in general. The sample answers confirmed through the statistical analysis that the research sample when the risk management has an important role in coordination between senior management and the rest of the departments for the availability of protection, and also have a role in training staff on all safety and risk management, and coordination between the suppliers of occupational safety equipment and maintenance Rotating them. There is no correlation between the insurance and risk management department and does not have any activity in the insurance awareness or the insurance manager may provide protection in the absence of risk management. The researcher presented a set of recommendations that can benefit from the research sample: Improving the efficiency of the performance of the company and the establishment and increasing the contribution of the service activity in the gross national product of Iraq. Insurance Department in the Iraqi Airways lacks the competence of the Department of Insurance, as the most staff in English language proficiency, because the insurance has a different privacy from the rest of the specialties. Building human capacity and developing the skills and ideas necessary to make the success of the risk management process to explain the types of risks and methods and address them. Involvement of Iraqi Airways employees in cooperation with insurance companies in training courses to identify all the latest developments in risk management, insurance and occupational safety and to identify the developments in civilized and advanced countries. the need to strengthen the service organization such as the airport at high levels of human qualifications in the specialties of insurance and occupational safety holders of higher degrees for the purpose of developing the risk management program.